PEMBUATAN BUKU PANDUAN MATA KULIAH CAPSTONE DESIGN DI JURUSAN TEKNIK MESIN UNIVERSITAS MATARAM - Fikrihadi Kurnia; Maharsa Pradityatama (Jurnal Abdi Insani, 2022)
Capstone design is one of the culmination courses that must be carried out by students. This course is carried out in the form of a project with a collection limit of 1 current semester. In the Department of Mechanical Engineering (JTM), Mataram University, it is carried out with a placement scheme in the Mechanical Planning course, 2 credits, and is carried out in Semester 5. This Manual is as a medium to help students complete projects on time and in accordance with the predetermined documentation format. In addition, the proposal of this book can be an added value in curriculum improvement and JTM accreditation. Determination of issues obtained from the results of discussions with the Head of the Department, Lecturers, and JTM Lecturers. Determination of priority issues is carried out using the ultrasound method (Urgency, Seriousness, Growth). Analysis of the root cause of the issue using the fishbone diagram method. As an evaluation of the results, an open seminar was conducted as an assessment of the quality of the capstone design manual. The result of this activity is the formation of a proposed draft manual for the capstone design course. The evaluation seminar is intended to measure the usability of the book in the major and the improvement needed. The results of making books have proven to have a positive impact on the major. The immediate impact that was felt was the use of this manual for filing the re-accreditation of the Department of Mechanical Engineering, University of Mataram. It is hoped that the implementation of this book can have another positive impact so as to improve the quality towards the implementation of the vision and mission of the department.